Socioeconomic status, sex, and obesity in a large national cohort of 15-87-year-old Open University students in Thailand - Sam Ang Seubsman (2018)
Background: As obesity increases, middle-income countries are undergoing a health-risk transition. We examine the association between socioeconomic status (SES) and emerging obesity in Thailand, and ascertain if an inverse relationship between SES and obesity has appeared. Methods: The data derived from 87 134 individuals (54% female; median age, 29 years) in a national cohort of distance-learning Open University students aged 15-87 years and living throughout Thailand. We calculated adjusted odds ratios for associations of SES with obesity (body mass index, ≥25) across 3 age groups by sex, after controlling for marital status, age, and urbanization. Results: Obesity increased with age and was more prevalent among males than females (22.7% vs 9.9%); more females were underweight (21.8% vs 6.2%). Annual income was 2000 to 3000 US dollars for most participants. High SES, defined by education, income, household assets, and housing type, associated strongly with obesity-positively for males and inversely for females-especially for participants younger than 40 years. The OR for obesity associated with income was as high as 1.54 for males and as low as 0.68 for females (P for trend <0.001). Conclusions: Our national Thai cohort has passed a tipping point and assumed a pattern seen in developed countries, ie, an inverse association between SES and obesity in females. We expect the overall population of Thailand to follow this pattern, as education spreads and incomes rise. A public health problem of underweight females could emerge. Recognition of these patterns is important for programs combating obesity. Many middle income countries are undergoing similar transitions. © 2009 by the Japan Epidemiological Association.